Man and his environment - Indera P. Singh (ed.); Tiwari , S.C. (ed.) (Delhi, 1980)
The content of the present volume deals with such diverse problems as environmental hazards to which man is exposed, physique and body compositions, physical fitness , nutritional studies, man and biosphere , island and isolates and urban and rural populations in a variety of environmental settings and ecosystems.
Keywords: Man-Influence of environment